1996
DOI: 10.1029/96gl00598
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the Kelvin‐Helmholtz instability by the transverse magnetic field in the Magnetosphere‐Ionosphere Coupling System

Abstract: A sheared flow equilibrium in the magnetosphereionosphere (M-I) coupling system and its stability against the Kelvin-Helmholtz (K-H) instability are investigated within the ideal MHD by using a box-shaped magnetospheric model. Without forcing, the unperturbed transverse (convection) electric field responsible for the E x B drift declines exponentially with time due to the ionospheric Joule dissipation and the decay (e-folding) time is larger than onehalf of the Alfv6n bounce period. The restoring force due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Although an abundance of heavy ions will affect the instability, heavy ions should primarily dampen the growth rates as they lead to a substantially broadened velocity shear region. The high growth rates are better explained, as predicted by the magnetohydrodynamic simulations of Miura and Kan [1992] and Miura [1996], by the lack of a conducting layer at the surface of the planet that can dissipate wave energy.…”
Section: Discussionmentioning
confidence: 91%
“…Although an abundance of heavy ions will affect the instability, heavy ions should primarily dampen the growth rates as they lead to a substantially broadened velocity shear region. The high growth rates are better explained, as predicted by the magnetohydrodynamic simulations of Miura and Kan [1992] and Miura [1996], by the lack of a conducting layer at the surface of the planet that can dissipate wave energy.…”
Section: Discussionmentioning
confidence: 91%
“…Some other factors are not cover by our current model with ideal MHD theory, e.g., Hall term of the MHD equations [ Huba , 1994; Thomas , 1995], and finite Larmor radius term [ Huba , 1996]. The contribution of ionosphere is not addressed, while Galinsky and Sonnerup [1994] and Miura [1996]have shown that the sufficiently large Pederson conductivity can slow down the development of the K‐H instability. More work is needed to improve the model and the understanding of the K‐H instability in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the actual magnetospheric equilibrium state in such a case must be determined by solving where V is the unperturbed flow velocity equal to the E × B drift velocity. This equilibrium state is not a steady state, because it decays with a decay time constant τ d , which is given by Miura [1996] by where τ A = 2ℓ/ V A is the Alfvén transit time with 2ℓ being the field line length from the ionosphere in one hemisphere to the ionosphere in the opposite hemisphere and V A being the average Alfvén speed in the magnetosphere.…”
Section: Discussionmentioning
confidence: 99%